"Two quid, chicken and chips, done": understanding what makes for young people's sense of living well in the city through the lens of fast food consumption. Issue 1 (2nd January 2022) - Burningham, Kate; Venn, Susan
ABSTRACT: Fast food seems unequivocally at odds with any moves towards more sustainable food consumption. It is identified as a major contributor to obesity, health inequalities, and to environmental impacts through its production and distribution. However, this problematisation of fast food ignores its contribution to understandings of "living well", particularly for young people. This paper draws on data from an international project which explores how young people understand what makes for living well in cities. We focus on research with young people in Lambeth, London, exploring the role of food – specifically fast food practices – in their constructions of living well. Drawing on focus group interviews and photo diaries with young people aged 12–24, we highlight the enthusiasm inherent in discussions of fast food whereby it is constructed as easily accessible, inexpensive and attractive, whilst affording young people a degree of autonomy and agency. Fast food outlets are regarded as friendly, convenient, and safe social spaces, in a context where austerity cuts have reduced access to spaces specifically for young people. Further, consumption of fast food facilitates and legitimises young people's use of local streets and green spaces. Thus practices of fast food consumption might be understood to contribute to the ability to "live well" from the perspective of young residents. Making fast food less accessible to young people may be part of obesity and sustainable food strategies, but a broader wellbeing strategy is needed which is informed by understanding the valued social practices fast food currently affords young people.